Nutritional status of adolescent girls in urban slums of Moradabad: a cross sectional study - Awasthi, Rashmi; Srivastava, Anurag; Dixit, Anil Kumar; Sharma, Mukesh (International Journal Of Community Medicine And Public Health, 2017)
Background: Adolescence is important and crucial period of transition from child-hood to adulthood identifies by WHO as the period from ages 10-19 years. Adolescence is marked as a period of growth spurt and maturation, determined not only by genetic and heredity factors alone but also depend on nutrition and access to health services. Nutritional status is now recognized to be a prime indicator of the health of individuals. So the present study was conducted develop a database on nutritional status of the adolescents of slums to enable the government and other non-governmental agencies to formulate policies and initiate strategies for the well-being of adolescent children. Methods:This cross sectional study was conducted for a period of one year from June 2013 to May 2014 in the urban slums of Moradabad district. 8 slums were selected by random sampling for the study. Simple random sampling was used to select the individuals from each slum. A total of 408 adolescent girls were interviewed on a pilot-tested, structured and predesigned schedule through oral questionnaire method. Data was statistically analyzed utilizing SPSS (version. 17.0) for Windows. Results: Maximum girls were in age group of 14-16 years (41.5%), followed by age group of 10-13 years (37.8%). 74.6% adolescents were found vegetarians. Out of 405 adolescent girls, 63 (15.6%) were underweight whereas only 14 (3.5%) were overweight No adolescent was found in obese category. Among vegetarian adolescent girls, 56 (18.5%) were underweight & 11 (3.6%) were overweight but among non-vegetarian adolescent girls this was only 7 (6.8%).This was found statistically significant. Conclusions:The study shows that the nutritional status of the study population has been severely affected by dietary habits and type of oil and salt used. Hence adoption of healthy dietary habits by all individuals is critical for the prevention of nutritional disorders.